Impacts of Reservoir on Groundwater Level and Quality in a Saline Area, Nakhon Panom Province, Thailand - Uma Seeboonruang (My University, 2012)
Saline soil is distributed widely in the northeast of Thailand. Groundwater is found to carry the dissolved salts from a deep underground to the soil surface and the evaporation dries the salts out leaving the white crust on the ground. Human activities commonly interrupt the balance of the subsurface system. One of the human factors is reservoir construction and operation. This study investigates the impacts of reservoir operation on the subsurface conditions in a saline soil in Thailand. Rainfall, water levels in the reservoir and down gradient of the reservoir, groundwater level and EC are monitored from December of 2011 to January of 2012. Statistical analysis is performed on this data. It can be concluded that the groundwater level in this study is correlated well with the water level in the reservoir. The rise of the groundwater level is not associated with the salinity in most of the area with some exception. These locations should be long term monitored as it shows the salinity risk toward the rise of the groundwater level and so the reservoir operation.
Keywords: Saline water; Groundwater and Watershed Analysis